2001
DOI: 10.1080/02791072.2001.10400482
|View full text |Cite
|
Sign up to set email alerts
|

Walking the Tightrope: Balancing Health and Drug Use

Abstract: This article stems from a study on San Francisco drug users and their health care experiences. Two hundred thirty-eight study participants were administered depth interviews and questionnaires to reveal a variety of health concerns and health behaviors. For these analyses, which focused on health practices and risky behaviors, the sample was divided into two groups: marijuana users, and other drug users (including methamphetamine, cocaine, heroin, and crack). The findings indicate that drug users behave simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The findings suggest that drug treatment clients report very similar self-care strategies to illicit drug users and general population samples (Boeri et al 2006;Drumm et al 2005;Duterte et al 2001;Hansson et al 2005).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The findings suggest that drug treatment clients report very similar self-care strategies to illicit drug users and general population samples (Boeri et al 2006;Drumm et al 2005;Duterte et al 2001;Hansson et al 2005).…”
Section: Discussionmentioning
confidence: 77%
“…Successful strategies included paid work, caring for children, limiting levels of drug use, and changing routes of administration. Similar strategies were found in research in San Francisco, which found illicit drug users reported other healthpromoting strategies such as sleeping and eating regularly, taking vitamins, exercising and practicing safe sex (Duterte et al 2001). The authors concluded that "the health practices of the study participants closely mirrored those of the general population" (p. 181).…”
mentioning
confidence: 60%
“…Knowledge of how to care for serious problems seemed to be a part of knowledge that was seen as necessary to survival on the streets. While many of these self-protective activities are not unique to drug users (Duterte et al, 2001), the use of these strategies shows that users play an active role in managing routine to serious health problems and injuries.…”
Section: Discussionmentioning
confidence: 99%
“…A popular notion remains that drug users are inherently uninterested in self-care. However, one study notes that health practices of drug users are similar to the general public in terms of eating and sleeping regularly, taking vitamins, and exercising (Duterte et al, 2001), but it does not address the types of foods drug users may consider healthy and how drug users remedy medical problems. Flavin's research (Flavin, 2002) challenges the perception of disinterest in self-care by exploring women's use of harm reduction techniques in an attempt to care for themselves during pregnancy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, a fatalistic attitude and low personal agency could be related to perceived inabilities to deal with life's hardships (Bolam, Hodgetts, Chamberlain, Murphy, & Gleeson, 2003) or even to levels of desperation among persons who use drugs (Meylakhs, Friedman, Mateu-Gelabert, Sandoval, & Meylakhs, 2015). Considering these perspectives, prevention programmes should focus on tailoring agency-based strategies to foster safer crack use practices (Wechsberg et al, 2004), since it has been demonstrated that persons who use drugs are concerned with taking care of their health and of themselves (Drumm et al, 2003;Duterte al., 2001;Gowan et al, 2012). One recognized method is peer involvement in harm reduction programmes (Marshall, Dechman, Minichiello, Alcock, & Harris, 2015;Mateu-Gelabert, al., 2014;Weeks et al, 2009) that train drug users as advocates.…”
Section: Discussionmentioning
confidence: 99%